2022
DOI: 10.1093/nar/gkac002
|View full text |Cite
|
Sign up to set email alerts
|

A phage parasite deploys a nicking nuclease effector to inhibit viral host replication

Abstract: PLEs (phage-inducible chromosomal island-like elements) are phage parasites integrated into the chromosome of epidemic Vibrio cholerae. In response to infection by its viral host ICP1, PLE excises, replicates and hijacks ICP1 structural components for transduction. Through an unknown mechanism, PLE prevents ICP1 from transitioning to rolling circle replication (RCR), a prerequisite for efficient packaging of the viral genome. Here, we characterize a PLE-encoded nuclease, NixI, that blocks phage development lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…Some of the newly discovered PLE variants, however, only appeared for a short time, such as PLE6, which was detected once in Bangladesh in 1987, and PLE8 in Vietnam in 1995 and 2004. We also detected one possible phage satellite with partial genetic relationship to PLEs, as has been described in non-cholera vibrios recently ( 25 ); however, its sequence could not be fully resolved from available data. It is highly likely that we still have not captured the full extent of PLE diversity and variant flux over time, as V. cholerae isolate sampling was sporadic and limited until recent decades (with over half of all isolates collected in only the last 9 years).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Some of the newly discovered PLE variants, however, only appeared for a short time, such as PLE6, which was detected once in Bangladesh in 1987, and PLE8 in Vietnam in 1995 and 2004. We also detected one possible phage satellite with partial genetic relationship to PLEs, as has been described in non-cholera vibrios recently ( 25 ); however, its sequence could not be fully resolved from available data. It is highly likely that we still have not captured the full extent of PLE diversity and variant flux over time, as V. cholerae isolate sampling was sporadic and limited until recent decades (with over half of all isolates collected in only the last 9 years).…”
Section: Resultsmentioning
confidence: 62%
“…Annotation and sequence comparison of open reading frames confirmed that the newly detected PLEs 6 to 10 possess genes key to PLE function that have been characterized in the previously studied PLEs 1 to 5. These include nixI , which encodes a nickase that interferes with ICP1’s ability to replicate ( 25 ), lidI , which can accelerate lysis of the V. cholerae host cell ( 22 ), and capR , which acts to repress ICP1’s capsid morphogenesis operon ( 21 ). The conservation of these genes indicates that the newly identified PLEs play roles similar to those of PLEs 1 to 5 as parasites of ICP1.…”
Section: Resultsmentioning
confidence: 99%
“…We detected decreased genome replication of both PLE and ICP1 and a delay in the timing of cell lysis when comparing PLEΔ sviR infection to PLE(+) infection (Figure S1). However, both lysis (Hays and Seed, 2019) and genome replication (Barth et al, 2020a; LeGault et al, 2022) are dependent on multiple PLE or ICP1 products, providing no clear candidate genes as targets of SviR regulation. We next pursued identifying target transcripts of SviR during ICP1 infection of PLE(+) V. cholerae .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, IS200/IS605 elements are associated with distal nucleases, which are guided by the transposable element-encoded sRNA. The ORF downstream of SviR, NixI, was recently shown to be a nicking endonuclease, implicated in the degradation of ICP1’s genome during rolling circle replication (LeGault et al, 2022). While NixI is not encoded within the transposable element repeats, the upstream sRNA proximal to a nuclease effector raises the possibility of a similar RNA-guided nuclease activity for NixI, secondary to the primary function as a replication inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation